Reaction type concrete waterproof material and preparation method thereof
By using microcapsule technology to wrap highly activated sodium carbonate in concrete waterproofing materials, and using the sustained release reaction of microcapsules, the problem that concrete waterproofing materials are difficult to be rigid and flexible during construction is solved, and the waterproof performance and durability of concrete are significantly improved.
Patent Information
- Application Number
- CN202510007441.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-03
- Publication Date
- 2025-04-11
AI Technical Summary
The existing concrete waterproof materials are difficult to have the advantages of rigid waterproofing and flexible waterproofing during construction, and the reaction of high-active masterbatches with cement leads to a decrease in application effect and waste of masterbatches.
Using reactive concrete waterproofing materials based on microcapsule technology, the active components are sustainably released to enhance waterproofing performance by wrapping highly active sodium carbonate inside SiO2 microcapsules and using different reactions of the microcapsules in the early and later stages of concrete molding.
It significantly improves the waterproof performance of concrete, with strong crack repair ability, long-term latency, permanent life, high density, and high bond strength and high volume stability with the substrate.
Smart Images

Figure CN119797795A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of concrete waterproof materials, in particular to a reactive concrete waterproof material based on microcapsule technology, and the preparation of the waterproof material. Background Art
[0002] The waterproofing ability of concrete structures not only has a decisive influence on the service life of concrete buildings, but is also crucial for maintaining the temperature and humidity environment inside the building, ensuring the normal progress of daily life and the smooth implementation of industrial production. In order to achieve good waterproofing ability of concrete structures, in addition to using building materials with high waterproofing ability, additional waterproofing measures need to be taken in the structural foundation, construction joints, basement facades, elevator shaft perimeters, roofs, underground structure top plates, and residential bathrooms and kitchens.
[0003] At present, commonly used waterproof materials are divided into two categories: organic waterproof materials and inorganic waterproof materials. Among them, inorganic waterproof materials are widely used because of their strong bonding with the concrete foundation, no need to use interface agents, and the same material as the concrete foundation (both are silicate materials), and the same lifespan as the foundation concrete. However, during the construction process, people often hope that the waterproof function of the concrete structure can have the advantages of both rigid waterproofing and flexible waterproofing, aiming to use the advantages of both inorganic and organic waterproof materials to achieve double protection. However, in practice, due to the poor performance of inorganic waterproof materials and the insufficient bonding between organic waterproof materials and the foundation, it is difficult to combine the two, and the waterproof measures eventually tend to fail.
[0004] In order to solve the defect that inorganic waterproof materials have high rigidity and poor deformation ability, which causes the waterproof layer to crack when the concrete structure cracks, thus causing serious damage to the waterproof ability, many scholars and research institutions have developed inorganic waterproof materials with built-in active components, such as permeable crystalline waterproof materials. Since the advent of this type of waterproof material in 1942, a series of product brands have been derived in Germany, Canada, the United States and Japan, such as VANDEX, XYPEX, PENETRON and PANDEX. Since entering the Chinese market for application in 1994, my country has also optimized and developed the product based on its performance. However, there are still difficult to solve technical problems in known permeable crystalline waterproof materials, such as the incompatibility of the active masterbatch, which causes the use of low-activity active masterbatch to have poor self-repairing effect, and the use of high-activity active masterbatch will react with cement, causing cement strength to decrease or masterbatch waste. Therefore, continuing to optimize inorganic waterproof materials has a positive significance for the development of concrete structure waterproofing projects. Summary of the invention
[0005] In order to solve the above-mentioned technical problems existing in concrete waterproof materials, the present invention has developed a reactive concrete waterproof material based on microcapsule technology, which utilizes the different reactions of microcapsules in the initial stage of concrete forming and the later curing process, so that the microcapsules can fully exert the role of active masterbatch, and solve the problems of reduced application effect and waste of masterbatch caused by the reaction of high-activity masterbatch with cement, thereby greatly improving the waterproof performance of concrete.
[0006] To achieve the above-mentioned purpose, the reactive concrete waterproof material provided by the present invention comprises sodium carbonate microcapsules, wherein the sodium carbonate microcapsules are microcapsules of sodium carbonate wrapped in silicon dioxide, and are prepared by a complex coagulation method with sodium carbonate as the core material and silicon dioxide as the wall material, and are denoted as Na 2 CO 3 @SiO 2 Microcapsules.
[0007] The present invention uses microcapsule technology to encapsulate highly active sodium carbonate in SiO 2 Inside the microcapsule, it is used as the active component of waterproof material. In the early stage of concrete forming, SiO 2 It can effectively prevent the free calcium ions in the concrete slurry from reacting with carbonate ions and prevent Na 2 CO 3 Rapid reaction leads to rapid hardening of cement; as SiO 2 Dissolve to generate Na 2 SiO 3 Sol can chelate free calcium ions in concrete (such as calcium in cement, lime and gypsum) to fill gaps; in the later curing process, Na 2 SiO 3 The calcium ions chelated by the sol gradually become free calcium ions, which, together with the free calcium ions in the concrete and NaCO 3 The reaction produces calcium carbonate CaCO 3 Crystallization achieves the purpose of further plugging cracks. Therefore, through the slow-release reaction of waterproof materials, the problems of reduced application effect and waste of masterbatch caused by the reaction of high-activity masterbatch with cement are solved, which greatly improves the durable waterproof performance of concrete, and has the advantages of strong crack repair ability, long-term latency, permanent life, high density, high bonding strength with the matrix and high volume stability.
[0008] As a limitation of the above technical solution, Na 2 CO 3 @SiO 2 The microcapsules were prepared by the following method: sodium carbonate was ground and dispersed in an ethanol-ammonia solution, tetraethoxysilane was added to form a suspension, and the suspension was stirred rapidly for a full reaction. During the reaction, tetraethoxysilane was hydrolyzed to generate SiO 2Polymerize on the surface of sodium carbonate to form Na 2 CO 3 @SiO 2 Microcapsules, and then vacuum dried to obtain Na 2 CO 3 @SiO 2 Microcapsule powder.
[0009] As a limitation of the above technical solution, the dosage ratio of sodium carbonate to tetraethoxysilane is (5:1) to (1:1) by mass.
[0010] As a limitation of the above technical solution, the raw material composition of the waterproof material also includes sodium hydroxide and quicklime.
[0011] After the waterproof material forms cement slurry, the NaOH, quicklime hydrolyzed to generate slaked lime, and Na 2 CO 3 @SiO2 microcapsules 2 Reaction occurs to make SiO 2 Dissolve to form Na with a network structure and cross-linking effect 2 SiO 3 sol, while slowly releasing Na 2 CO 3 , with SiO 2 The continuous dissolution and slow release of CO 3 2- The ions then react with the free calcium ions in the concrete to form insoluble CaCO 3 , to achieve the purpose of further blocking.
[0012] As a limitation of the above technical solution, the raw material composition of the waterproof material also includes silicate cement, and preferably, silicate cement with a strength grade not less than 42.5 is selected.
[0013] As a limitation of the above technical scheme, the waterproof material includes the following raw material components in parts by weight: 20 to 50 parts of quartz powder, 5 to 10 parts of sodium carbonate microcapsule powder, 0.1 to 1 part of water reducer, 1 to 5 parts of sodium hydroxide, 1 to 5 parts of volcanic ash, 1 to 5 parts of quicklime, 1 to 10 parts of anhydrous gypsum, 0.1 to 1 part of hydroxypropyl cellulose, 0.1 to 5 parts of citric acid, and silicate cement is supplemented to 100 parts.
[0014] As a limitation of the above technical solution, the water reducer is a sodium polycarboxylate water reducer.
[0015] As a limitation of the above technical solution, the quartz powder is selected from 50-300 mesh graded sand; the fineness of the volcanic ash is not less than 800 mesh; the CaO content of the quicklime is greater than 85%, and the fineness is not less than 200 mesh; the fineness of the sodium hydroxide, anhydrous gypsum, hydroxypropyl cellulose, and citric acid are not less than 40 mesh.
[0016] Further improve the raw material component formula of reactive concrete waterproofing materials and optimize rigid cement-based waterproofing materials.
[0017] The present invention also provides a method for preparing the reactive concrete waterproof material as described above, comprising the following preparation steps:
[0018] 1) Preparation of sodium carbonate microcapsules: Grind the sodium carbonate, specifically, grind the sodium carbonate using a ceramic abrasive and a planetary ball mill, and then disperse it in an ethanol-ammonia solution to form a suspension, add tetraethoxysilane, and stir the reaction for 12 to 24 hours to generate SiO 2 Aggregation on the surface of sodium carbonate forms Na 2 CO 3 @SiO 2 The microcapsules were centrifuged and washed several times, and then vacuum dried to obtain Na 2 CO 3 @SiO 2 Microcapsule powder; the mass ratio of sodium carbonate to tetraethoxysilane is (5:1) to (1:1);
[0019] 2) All raw material components are weighed and mixed, and homogenized using a ball mill to obtain a reactive concrete waterproof material.
[0020] As a limitation of the above technical solution, the volume ratio of ethanol to ammonia water in the ethanol-ammonia water solution is (199:1) to (190:10).
[0021] The sodium carbonate microcapsules, which are the active component of the waterproof material of the present invention, have simple preparation operations and stable products. The preparation of the waterproof material only requires mixing and homogenizing, which is beneficial to production and application.
[0022] In summary, the reactive concrete waterproof material of the present invention is a rigid cement-based waterproof material, which is suitable for waterproofing projects of concrete structures and has the following beneficial effects:
[0023] (1) Strong crack repairing ability: After dissolving, the components of the waterproof material of the present invention migrate into the concrete microcracks and matrix, and the formed sodium silicate and sodium carbonate react with the free calcium ions in the concrete, thereby generating water-insoluble hydration products, namely calcium silicate and calcium carbonate, in the cracks and pores of the matrix, thereby achieving the purpose of crack repairing and strengthening the matrix;
[0024] (2) Long-term latency: Among the raw materials of waterproof materials, except for water reducers (used to improve the workability of slurry during the mixing stage), other raw materials are inorganic materials. If they are not completely consumed, they can exist in the pores of the coating and the substrate for a long time, even for several years. When the concrete substrate cracks and external water penetrates, they are activated and react again.
[0025] (3) Permanent life: Since the hydration products generated are silicates and carbonates, which have the same composition as the base concrete, they have the same life as concrete;
[0026] (4) High density: The hydration products generated are mostly silicate and carbonate gels, which can fill concrete cracks and thus have high density. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 , is a scanning electron microscope photograph of the sodium carbonate microcapsule of the present invention;
[0028] Figure 2 , are photos of cracks being repaired by the waterproof material of the present invention.
[0029] Figure 3 , is the XRD diagram of the overflow crack repair component. DETAILED DESCRIPTION
[0030] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0031] The raw materials used in the following examples and comparative examples are typical products purchased from the market.
[0032] Example
[0033] The following embodiments are all reactive concrete waterproof materials based on sodium carbonate microcapsules.
[0034] Example 1
[0035] The raw material composition of the reactive concrete waterproof material (by mass): 50 parts of silicate cement (PO 42.5), 35 parts of quartz powder (100 mesh), 5 parts of sodium carbonate microcapsule powder, 0.3 parts of sodium polycarboxylate water reducer (Sika 540P), 2 parts of sodium hydroxide (40 mesh), 2 parts of volcanic ash (1000 mesh), 2 parts of quicklime (CaO content greater than 85%, 200 mesh), 2 parts of anhydrous gypsum (200 mesh), 0.2 parts of hydroxypropyl cellulose (80 mesh), and 1.5 parts of citric acid (40 mesh).
[0036] Wherein, the preparation of sodium carbonate microcapsules is carried out as follows:
[0037] Take 100 g of sodium carbonate, grind it with a planetary ball mill using ceramic mortar as an abrasive, and then disperse it in 2 L of ethanol-ammonia solution (the volume ratio of ethanol to ammonia solution is 195:5). After forming a suspension, add 50 g of tetraethoxysilane and stir rapidly for 12 to 24 hours to hydrolyze the generated SiO 2 Polymerize on the surface of sodium carbonate to form Na 2 CO 3 @SiO 2 Microcapsules, the appearance of which is shown in the attached Figure 1 After centrifugation, ethanol and water were used to wash in sequence, and then vacuum dried to obtain Na 2 CO 3 @SiO 2 Microcapsule powder.
[0038] The steps for preparing waterproof materials are as follows:
[0039] (1) All raw materials are accurately measured;
[0040] (2) placing the raw materials of each component measured in step (1) into a mixer for a first stirring for 10 to 15 minutes to obtain a stirred mixture;
[0041] (3) placing the stirred mixture obtained in step (2) into a ball mill for a second stirring and ball milling for 30 to 40 minutes to obtain a reactive concrete waterproof material;
[0042] (4) The reactive concrete waterproofing material is packaged on a packaging machine in a container having good airtightness and capable of preventing the entry of outside air and moisture, thereby obtaining a reactive concrete waterproofing agent product.
[0043] Example 2
[0044] The raw material composition of the reactive concrete waterproof material (by mass): 40 parts of silicate cement (PO 42.5), 45 parts of quartz powder (100 mesh), 5 parts of sodium carbonate microcapsule powder, 0.2 parts of sodium polycarboxylate water reducer (Sika 540P), 1.5 parts of sodium hydroxide (40 mesh), 2.5 parts of volcanic ash (800 mesh), 3 parts of quicklime (CaO content greater than 85%, 200 mesh), 1 part of anhydrous gypsum (200 mesh), 0.1 parts of hydroxypropyl cellulose (80 mesh), and 1.7 parts of citric acid (40 mesh).
[0045] Wherein, the preparation of sodium carbonate microcapsules is carried out as follows:
[0046] 100 g of sodium carbonate was taken and ground with a planetary ball mill using ceramic mortar as an abrasive. Then, the sodium carbonate was dispersed in 2 L of ethanol-ammonia solution (the volume ratio of ethanol to ammonia solution was 196:4). After forming a suspension, 60 g of tetraethoxysilane was added and the suspension was rapidly stirred for 12 to 24 hours to hydrolyze the generated SiO 2 Polymerize on the surface of sodium carbonate to form Na 2 CO 3 @SiO 2 The microcapsules were centrifuged and washed with ethanol and water in sequence, and then dried in vacuum to obtain Na 2 CO 3 @SiO 2 Microcapsule powder.
[0047] The waterproof material was prepared in the same manner as in Example 1 to obtain a reactive concrete waterproofing agent product.
[0048] Example 3
[0049] The raw material composition of the reactive concrete waterproof material (by mass): 35 parts of silicate cement (PO 42.5), 45 parts of quartz powder (150 mesh), 6 parts of sodium carbonate microcapsule powder, 0.2 parts of sodium polycarboxylate water reducer (Sika 540P), 3 parts of sodium hydroxide (40 mesh), 3 parts of volcanic ash (1000 mesh), 3 parts of quicklime (CaO content greater than 85%, 200 mesh), 3 parts of anhydrous gypsum (200 mesh), 0.2 parts of hydroxypropyl cellulose (80 mesh), and 1.6 parts of citric acid (40 mesh).
[0050] Wherein, the preparation of sodium carbonate microcapsules is carried out as follows:
[0051] 100 g of sodium carbonate was taken and ground with a planetary ball mill using ceramic mortar as an abrasive. Then, the sodium carbonate was dispersed in 2 L of ethanol-ammonia solution (the volume ratio of ethanol to ammonia solution was 197:3). After forming a suspension, 40 g of tetraethoxysilane was added and the suspension was rapidly stirred for 12 to 24 hours to hydrolyze the generated SiO 2 Polymerize on the surface of sodium carbonate to form Na 2 CO 3 @SiO 2 The microcapsules were centrifuged and washed with ethanol and water in sequence, and then dried in vacuum to obtain Na 2 CO 3 @SiO 2 Microcapsule powder.
[0052] The waterproof material was prepared in the same manner as in Example 1 to obtain a reactive concrete waterproofing agent product.
[0053] Example 4: 54 parts of silicate cement (PO 42.5), 30 parts of quartz powder (150 mesh), 5 parts of sodium carbonate microcapsule powder, 0.3 parts of sodium polycarboxylate water reducer (Sika 540P), 2 parts of sodium hydroxide (40 mesh), 3 parts of volcanic ash (1000 mesh), 2.5 parts of quicklime (200 mesh), 1.5 parts of anhydrous gypsum (200 mesh), 0.2 parts of hydroxypropyl cellulose (80 mesh), and 1.5 parts of citric acid (40 mesh).
[0054] Wherein, the preparation of sodium carbonate microcapsules is carried out as follows:
[0055] 100 g of sodium carbonate was taken and ground with a planetary ball mill using ceramic mortar as an abrasive. Then the sodium carbonate was dispersed in 2 L of ethanol-ammonia solution (the volume ratio of ethanol to ammonia solution was 195:5). After forming a suspension, 80 g of tetraethoxysilane was added and the suspension was rapidly stirred for 12 to 24 hours to hydrolyze the generated SiO 2 Polymerize on the surface of sodium carbonate to form Na 2 CO 3 @SiO 2 The microcapsules were centrifuged and washed with ethanol and water in sequence, and then dried in vacuum to obtain Na 2 CO 3 @SiO 2 Microcapsule powder.
[0056] The waterproof material was prepared in the same manner as in Example 1 to obtain a reactive concrete waterproofing agent product.
[0057] According to the requirements of GB 18445-2012 "Cement-based penetrating crystalline waterproof material", the compression, flexural and impermeability properties of each waterproofing agent in Examples 1 to 4 were tested. The results are shown in Table 1 below.
[0058]
[0059] Note: The 28d impermeability pressure of the benchmark concrete is 0.4MPa
[0060] Figure 2 This is a microscopic image of a crack repaired with the waterproofing agent of the present invention. It can be seen that the crack is filled with white crystals. The white crystals are removed and subjected to XRD research. Figure 3 As shown, it is proved that the overflow component is CaCO 3 , which as a mobile component can quickly repair concrete cracks.
[0061] Comparative Example 1
[0062] This comparative example is a sodium carbonate-free waterproofing agent commonly used in concrete structures, and the specific raw material components are as follows:
[0063] 53 parts of silicate cement (PO 42.5), 37 parts of quartz powder (100 mesh), 0.3 parts of sodium polycarboxylate water reducer (Sika 540P), 2 parts of sodium hydroxide (40 mesh), 2 parts of volcanic ash (1000 mesh), 2 parts of quicklime (200 mesh), 2 parts of anhydrous gypsum (200 mesh), 0.2 parts of hydroxypropyl cellulose (80 mesh), 1.5 parts of citric acid (40 mesh). Stir the above powders for 10-15 minutes and ball mill for 30-40 minutes to obtain a waterproofing agent.
[0064] Comparative Example 2
[0065] The concrete waterproof material of this comparative example also uses sodium carbonate microcapsules, but is not compounded with alkali (specifically sodium hydroxide and quicklime). The specific raw material components are as follows:
[0066] 52 parts of silicate cement (PO 42.5), 37 parts of quartz powder (100 mesh), 5 parts of sodium carbonate microcapsule powder (same as Example 1), 0.3 parts of sodium polycarboxylate water reducer (Sika 540P), 2 parts of volcanic ash (1000 mesh), 2 parts of anhydrous gypsum (200 mesh), 0.2 parts of hydroxypropyl cellulose (80 mesh), and 1.5 parts of citric acid (40 mesh). The above powders are stirred for 10 to 15 minutes and ball-milled for 30 to 40 minutes to obtain a waterproofing agent.
[0067] Comparative Example 3
[0068] The concrete waterproof material of this comparative example uses conventional sodium carbonate and silicon dioxide, and the specific raw material components are as follows:
[0069] 55 parts of silicate cement (PO 42.5), 30 parts of quartz powder (100 mesh), 3 parts of sodium carbonate (100 mesh), 1 part of nano silicon dioxide (Annaiji Chemical, 40nm), 0.3 parts of sodium polycarboxylate water reducer (Sika 540P), 2 parts of sodium hydroxide (40 mesh), 3 parts of volcanic ash (1000 mesh), 2.5 parts of quicklime (200 mesh), 1.5 parts of anhydrous gypsum (200 mesh), 0.2 parts of hydroxypropyl cellulose (80 mesh), and 1.5 parts of citric acid (40 mesh). The above powders were stirred for 10 to 15 minutes and ball-milled for 30 to 40 minutes to obtain a waterproofing agent.
[0070] According to the requirements of GB 18445-2012 "Cement-based penetrating crystalline waterproof material", the compression, flexural and impermeability properties of the waterproofing agents of Comparative Examples 1 to 3 were tested. The results are shown in Table 2 below.
[0071]
[0072] Note: The 28d impermeability pressure of the benchmark concrete is 0.4MPa
[0073] Comparing the performance data of the examples and comparative waterproofing agents in Tables 1 and 2, it can be seen that in the case where no sodium carbonate is added to comparative example 1, since CaCO cannot be generated in the end, 3 The crystallization of the concrete resulted in its anti-seepage pressure being much lower than that of the embodiment; although the comparative example 2 added sodium carbonate microcapsules, it was not combined with a strong base, resulting in the sodium carbonate microcapsules being unable to dissolve, and the internal sodium carbonate being difficult to release, and its anti-seepage pressure was also lower than that of the embodiment; although the comparative example 3 added sodium carbonate and nano-silicon dioxide, the sodium carbonate was not protected, resulting in it reacting with the matrix itself during concrete molding, thereby making its anti-seepage pressure lower than that of the embodiment. The reactive concrete waterproof material of the present invention has significantly improved compression resistance, flexural resistance and anti-seepage performance.
[0074] In summary, the reactive concrete waterproof material of the present invention is a rigid cement-based waterproof material having the advantages of strong crack repairing ability, long-term latency, permanent life, high density, high bonding strength with the matrix and high volume stability, and is suitable for waterproofing projects of concrete structures.
Claims
1. A reactive concrete waterproof material, characterized in that: The raw material components of the waterproof material include sodium carbonate microcapsules, which are microcapsules of sodium carbonate wrapped in silicon dioxide. They are prepared by a complex coagulation method with sodium carbonate as the core material and silicon dioxide as the wall material, and are recorded as Na2CO3@SiO2 microcapsules.
2. The reactive concrete waterproof material according to claim 1, characterized in that: Na2CO3@SiO2 microcapsules were prepared by the following method: Sodium carbonate is ground and dispersed in an ethanol-ammonia solution to form a suspension, and tetraethoxysilane is added thereto. The suspension is stirred to react to obtain Na2CO3@SiO2 microcapsules formed by the polymerization of SiO2 on the surface of sodium carbonate. The microcapsules are then vacuum dried to obtain Na2CO3@SiO2 microcapsule powder.
3. The reactive concrete waterproof material according to claim 2, characterized in that: The dosage ratio of sodium carbonate to tetraethoxysilane is (5:1) to (1:1) by mass.
4. The reactive concrete waterproof material according to claim 1, characterized in that: The raw materials of waterproof materials also include sodium hydroxide and quicklime.
5. The reactive concrete waterproof material according to claim 1, characterized in that: The raw material composition of the waterproof material also includes silicate cement. Preferably, silicate cement with a strength grade not less than 42.5 is selected.
6. The reactive concrete waterproof material according to any one of claims 1 to 5, characterized in that: The waterproof material includes the following raw material components in parts by weight: 20-50 parts of quartz powder, 5-10 parts of sodium carbonate microcapsule powder, 0.1-1 part of water reducing agent, 1-5 parts of sodium hydroxide, 1-5 parts of volcanic ash, 1-5 parts of quicklime, 1-10 parts of anhydrous gypsum, 0.1-1 part of hydroxypropyl cellulose, 0.1-5 parts of citric acid, and silicate cement is supplemented to 100 parts.
7. The reactive concrete waterproof material according to claim 6, characterized in that: The water reducing agent is a sodium polycarboxylate water reducing agent.
8. The reactive concrete waterproof material according to claim 6, characterized in that: The quartz powder is made of graded sand of 50-300 meshes; the fineness of the volcanic ash is not less than 800 meshes; the CaO content of the quicklime is greater than 85%, and the fineness is not less than 200 meshes; the fineness of the sodium hydroxide, anhydrous gypsum, hydroxypropyl cellulose and citric acid are all not less than 40 meshes.
9. A method for preparing a reactive concrete waterproof material as claimed in any one of claims 1 to 8, characterized in that: The method comprises the following preparation steps: 1) Preparing sodium carbonate microcapsules: grinding sodium carbonate, and then dispersing it in an ethanol-ammonia solution, adding tetraethoxysilane to form a suspension, stirring and reacting for 12 to 24 hours to generate SiO2 that polymerizes on the surface of sodium carbonate to form Na2CO3@SiO2 microcapsules, centrifuging and washing for multiple times, and then vacuum drying to obtain Na2CO3@SiO2 microcapsule powder; the amount ratio of sodium carbonate to tetraethoxysilane is (5:1) to (1:1) by mass; 2) All raw material components are weighed, mixed and homogenized to obtain a reactive concrete waterproof material.
10. The method for preparing the reactive concrete waterproof material according to claim 9, characterized in that: The volume ratio of ethanol to ammonia water in the ethanol-ammonia water solution is (199:1) to (190:10).